Market driven power plant investment perspectives in Europe: Climate policy and technology scenarios until 2050 in the Model EMELIE-ESY - Andreas Schröder; Thure Traber; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
EMELIE-ESY is a partial equilibrium model with focus on electricity markets. Private investors optimize their generation capacity investment and dispatch over the horizon 2010 to 2050. In the framework of the Energy Modeling Forum 28, we investigate how climate policy regimes affect market developments under different technology availabilities and climate policies on the European power markets. The model projects an only minor increase of power consumption because of higher wholesale prices or energy efficiency current climate policy, and a balanced consumption pathway under ambitious climate policy. These results contrast with findings of POLES and PRIMES models in the reference case that predict unexpected heavy consumption increases by 2050. By contrast, we find no investment into Carbon Capture and Storage (CCS) and a diminishing share of nuclear energy. We find that renewable energy supply extension as projected can sufficiently meet electricity consumption complemented by only few capacity investments in conventional technology.
Keywords: 330; electricity markets; investment; climate policy